Double Lap Shear Testing of Coating-Modified Ice Adhesion to Specific Shuttle Component Surfaces - Ferrick, Michael G.; Mulherin, Nathan D.; Coutermarsh, Barry A.; Durell, Glenn D.; Curtis, Leslie A.; St. Clair, Terry L.; Weiser, Erik S.; Cano, Roberto J.; Smith, Trent M.; Stevenson, Charles G.; Martinez, Eloy C. (2006)
The goals of this experimental program were to optimize the effectiveness of an icephobic coating for use on several Space Shuttle surfaces, to evaluate the effects of adding an ultraviolet light absorber (UVA) on coating performance, and to assess the consistency and durability of the basic coating and its modifications. The double lap shear test was used to quantify ice adhesion performance at a constant temperature of 112 C ( 170 F). The experiments used ice that was grown as strong and consistently as possible before being subjected to the extreme temperature decrease. Standardized coating application with a foam brush provided consistent and reproducible surface coverage. The program included 20 tests subdivided in two phases. Phase 1 focused on determining an optimal coating of Rain-X and varying weight fractions of PTFE powders MP-55 and UF-8TA. Ice adhesion to the UF-8TA coatings was similar to that of the uncoated controls. Conversely, the MP-55 coatings produced large reductions in ice adhesion. Through three cycles of phase 1 testing the M4 coating, a mixture of 60% Rain-X with 40% MP- 55, was the best and most consistent by a wide margin. As a result, M4 was the basis of all phase 2 mixes. Phase 2 tests sought to verify the effectiveness and durability of the optimal coating for several surfaces on the shuttle and to quantify any changes in effectiveness resulting from the addition of UVA to the coating. The ice adhesion to coated coupons with Koropon, Kapton tape, Kapton film, and Fire-X (fire-retardant paint) surfaces was a small fraction of the adhesion to corresponding uncoated coupons. Rain-X solvent loss during prolonged coating preparation caused a greater increase in ice adhesion than that of adding the UVA. A rapid mixing procedure was developed to minimize this problem. The M4 coating showed outstanding performance and durability through five cycles of ice growth and adhesive failure. The original document contains color images.